Tsc3p Is an 80-Amino Acid Protein Associated with Serine Palmitoyltransferase and Required for Optimal Enzyme Activity - Gable, Ken; Slife, Harry; Bacikova, Dagmar; Monaghan, Erin; Dunn, Teresa M. (The Journal of biological chemistry, 2000)
Serine palmitoyltransferase catalyzes the first step of sphingolipid synthesis, condensation of serine and palmitoyl CoA to form the long chain base 3-ketosphinganine. TheLCB1/TSC2 and LCB2/TSC1 genes encode homologous proteins of the α-oxoamine synthase family required for serine palmitoyltransferase activity. The other α-oxoamine synthases are soluble homodimers, but serine palmitoyltransferase is a membrane-associated enzyme composed of at least two subunits, Lcb1p and Lcb2p. Here, we report the characterization of a third gene,TSC3, required for optimal 3-ketosphinganine synthesis inSaccharomyces cerevisiae. S. cerevisiae cells lacking theTSC3 gene have a temperature-sensitive lethal phenotype that is reversed by supplying 3-ketosphinganine, dihydrosphingosine, or phytosphingosine in the growth medium. The tsc3 mutant cells have severely reduced serine palmitoyltransferase activity. TheTSC3 gene encodes a novel 80-amino acid protein with a predominantly hydrophilic amino-terminal half and a hydrophobic carboxyl terminus that is membrane-associated. Tsc3p coimmunoprecipitates with Lcb1p and/or Lcb2p but does not bind as tightly as Lcb1p and Lcb2p bind to each other. Lcb1p and Lcb2p remain tightly associated with each other and localize to the membrane in cells lacking Tsc3p. However, Lcb2p is unstable in cells lacking Lcb1p and vice versa.